Administrative Capacity as a Constraint to Fiscal Decentralization. The Case of Romania and Poland - Dana Georgeta Alexandru; Beata Guziejewska (Comparative Economic Research. Central and Eastern Europe, 2020)
This paper considers the problem of administrative capacity as one of the main requirements that the accession countries seeking EU membership had to meet, and as a prerequisite to the decentralization of their public sectors and public finances. The selected decentralization problems are analyzed using the cases of two countries: Romania and Poland. The results of a theoretical and practical evaluation of administrative capacity as a likely obstacle to fiscal decentralization are presented taking account of the different levels of decentralization in Poland and Romania. A comparative analysis of Romania and Poland shows that administrative capacity can be a constraint for fiscal decentralization. In Poland, the main problem is that the local authorities have not yet been granted powers over taxes that are more complicated to administer in legal and financial terms. Romania has the problem of the incomplete devolution of powers and the limited financial independence of local governments, which basically means that the principle of subsidiarity is insufficiently implemented.
Keywords: H70; H71; H77; 330; public administration; local taxes; fiscal decentralization; local selfgovernment